400MPa-class corrosion-resistant rebar and its production method
A 400 MPa-class rebar with a controlled chemical composition and microstructure addresses premature corrosion in reinforced concrete structures, offering superior corrosion resistance and weldability while reducing costs, suitable for marine environments.
Patent Information
- Application Number
- JP2023543025
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-15
- Filing Date
- 2021-04-12
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-04-12
AI Technical Summary
Reinforced concrete structures in harsh environments suffer from premature corrosion due to damage to the passive film on rebar surfaces, leading to structural failure, and existing solutions like corrosion inhibitors and stainless steel rebars are costly and have welding issues.
A 400 MPa-class corrosion-resistant rebar with a specific chemical composition (Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.50%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%) and a microstructure of ferrite and bainite, produced through controlled processes to ensure excellent corrosion resistance, mechanical performance, and weldability.
The rebar exhibits improved corrosion resistance by 45 times over HRB400, maintains strong weld structures, and reduces production costs, making it suitable for marine construction with enhanced mechanical properties and economic benefits.
Smart Images

Figure 0007655658000001 
Figure 0007655658000002 
Figure 0007655658000003
Abstract
Description
[Technical field]
[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to a Chinese patent application filed on January 15, 2021, with application number 202110051522.4 and titled "400 MPa-class corrosion-resistant rebar and its production method," the entire contents of which are incorporated herein by reference.
[0002] The present invention belongs to the field of metallurgy, and relates to a 400 MPa corrosion-resistant rebar and a method for producing the same. [Background technology]
[0003] Reinforced concrete structures are the most widely used structural form in infrastructure construction, and although the theoretical service life of reinforced concrete structures is long, in actual construction, there are many cases of premature failure of reinforced concrete, which not only increases maintenance costs but also leads to a huge waste of energy and resources. Research has shown that coastal reinforced concrete structures are subject to poor environments such as environments rich in chloride ions and sulfates, and high temperature and humidity, so that after only 10 to 15 years of construction, serious corrosion damage occurs widely and commonly, far from reaching the theoretical service life designed.
[0004] The concrete of reinforced concrete structure belongs to a strong alkaline environment, in which the surface of the rebar is passivated to produce a stable metal oxide passive film. In the practical use of reinforced concrete structure, the dissolution and repair of the passive film are theoretically in a balanced state, so that the electric potential at each position on the surface of the rebar is almost the same, and it is guaranteed that the rebar is not easily corroded or has a very low corrosion rate. However, when the passive film on the surface of the rebar is damaged by external erosive substances, for example, in a marine environment, when the active chloride ions on the passive film on the surface of the rebar reach a certain concentration, the dissolution and repair of the passive film will be unbalanced, and the dissolution of the passive film will be accelerated to form a corrosion pit, which will result in the rebar skeleton being exposed to the erosive medium, and ultimately lead to the failure of the reinforced concrete structure.
[0005] At present, corrosion inhibitors, surface protective layers, cathodic protection, rebar painting and other methods have been effective to a certain extent in extending the service life of reinforced concrete structures. However, improving the corrosion resistance of the steel bars themselves, which are the core of reinforced concrete structures, is the key to solving the corrosion damage problem of reinforced concrete structures.
[0006] In addition to corrosion resistance, the mechanical performance, welding performance, production and manufacturing costs of rebars are also important aspects that affect the actual production and application of rebars. For example, stainless steel rebars are a common rebar type with excellent corrosion resistance. By adding a large amount of alloying elements such as Cr, Ni, and Mo, the corrosion resistance can be significantly improved compared to ordinary carbon steel rebars, and the corrosion resistance is very good. However, because stainless steel rebars contain a large amount of alloying elements, their welding performance is very poor, and in actual construction, the welding construction cost of stainless steel rebars is very high, and there is a risk that reinforced concrete structures will be unstable due to poor welding. In addition, because stainless steel rebars contain a large amount of alloying elements, their raw material costs and production costs are multiplied by several times compared to ordinary rebars, resulting in expensive and insufficient for wide application, which does not meet the social demand for energy saving and consumption reduction. In addition, there is still debate as to whether macrocell corrosion will occur when stainless steel rebars and ordinary rebars are lap-spliced.
[0007] Therefore, how to simultaneously ensure corrosion resistance, mechanical performance, welding performance, and cost is an important issue in the research of corrosion-resistant rebars, which has significant social significance and economic effects. Summary of the Invention
[0008] In order to solve the technical problems existing in the prior art, the present invention aims to provide a 400 MPa class corrosion-resistant rebar which has excellent corrosion resistance, comprehensive mechanical performance and welding performance, can be manufactured at low material and process costs, and is suitable for wide use in marine construction.
[0009] In order to achieve the object of the invention, in one embodiment, the chemical components are, in mass percent, Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.5%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦ The present invention provides a 400 MPa class corrosion-resistant reinforcing bar containing 0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%, Cr+Mo+0.5Mn+0.35Ni+0.25Cu being 11.1-12.2%, C+N+0.3Si+Mn+1.8Nb being 0.4-0.8%, and the balance being Fe and unavoidable impurities.
[0010] Preferably, the chemical components of the reinforcing bar further include, in mass percent, any one or more of V: 0.1-0.15%, Ti: 0.01-0.05%, Al: 0.01-0.03%, and B: 0.0005-0.0020%.
[0011] Furthermore, the microstructure of the reinforcing bar is ferrite and bainite, with the proportion of ferrite being 28% to 40%.
[0012] Furthermore, the reinforcing bar has a grade of A, B, C and D inclusions of ≦1.0 in the GB / T10561 standard.
[0013] Additionally, the rebar has a yield strength of ≧420 MPa, a tensile strength of ≧540 MPa, an elongation at break of ≧18%, and a total elongation at maximum force of ≧7.5%.
[0014] Preferably, the nominal diameter of the reinforcing bar is 6 to 32 mm.
[0015] Preferably, when the nominal diameter of the reinforcing bar is 6 to 10 mm, the reinforcing bar is a coil reinforcing bar, and when the nominal diameter of the reinforcing bar is 12 to 32 mm, the reinforcing bar is a rod reinforcing bar.
[0016] Furthermore, in an ambient immersion corrosion test, the corrosion rate based on the average weight loss of the reinforcing bar is 0.05 to 0.1 g / (m2 h), and in a salt spray corrosion test, the average weight loss of the reinforcing bar is The corrosion rate due to loss is 0.01 to 0.04 g / (m 2 h) and In simulated concrete pore water with a chloride ion concentration of ≧3 mol / L, the self-corrosion potential of the reinforcing bar is -0.1 to -0.15 V and the polarization resistance is 2500 to 3000 kΩ / cm 2 in, Self-corrosion current density is ≦0.13μA / cm 2 It is.
[0017] Preferably, the reinforcing bar can be produced using either process route 1 or process route 2; The process path 1 includes a hot metal pre-desulfurization process, a converter smelting process, an AOD furnace refining process, an LF furnace refining process, a square billet continuous casting process, a hot continuous rolling process, and a temperature controlled cooling process, which are performed in sequence. The process path 2 includes a hot metal pre-desulfurization process, a converter smelting process, an LF furnace refining process, an RH furnace refining process, a square billet continuous casting process, a hot continuous rolling process, and a temperature controlled cooling process, which are performed in sequence.
[0018] Preferably, in the process route 1, the tapping temperature in the converter smelting step is 1600-1660°C, and during the AOD furnace refining step, a high carbon ferrochromium alloy and a molybdenum iron alloy are added to the molten steel to perform initial alloying of the molten steel, and after reduction and slag removal, a manganese alloy is added, the tapping ladle is purged with argon for 5 minutes or more before tapping, 20 kg of aluminum ingot is added to the molten steel during tapping, the tapping temperature is 1630-1670°C, and the tapping C content is ≦0.01%, and the LF furnace refining step In this case, after the molten steel reaches the ladle of the LF furnace, the slag is adjusted by adding 13-15 kg of lime and 4.0-6.5 kg of fluorite per ton of molten steel, the white slag holding time is ≧8 min, the soft stirring time is 8-15 min, the tapping temperature is 1600-1620°C, and in the square billet continuous casting process, carbon-free mold flux or ultra-low carbon mold flux is used, the continuous casting temperature is 1520-1560°C, and the casting speed during continuous casting is 1.2-1.6 m / min.
[0019] Preferably, in the process route 2, during the converter smelting step, a trace carbon ferrochromium alloy is added to the molten steel during tapping to perform initial alloying of the molten steel, and the tapping temperature is 1700-1750°C; during the LF furnace refining step, argon is bottom-blown into the ladle of the LF furnace at a flow rate of 80-160 L / min throughout the entire process, and the tapping temperature is 1560-1600°C; and during the RH furnace refining step, oxygen blowing into the RH furnace is started after the RH furnace is evacuated for 3 min, and the total amount of oxygen blown is 500-700 Nm 3 Then, the molten steel is added with trace carbon ferrochrome. A molten steel is alloyed by adding a tungsten alloy, and when the vacuum level is less than 2 mbar, fresh water circulation is performed for 5 minutes or more, the tapping temperature is 1560-1600°C, and the tapping C content is ≦0.015%. In the square billet continuous casting process, a carbon-free mold flux or an ultra-low carbon mold flux is used, the continuous casting temperature is 1520-1560°C, and the casting speed during continuous casting is 2.2-2.6 m / min.
[0020] Preferably, in both process path 1 and process path 2, In the hot continuous rolling process, the continuous cast billet is heated in a heating furnace, the heating temperature is 1100 to 1200°C, the furnace time is 60 to 120 minutes, and then rolled into a rod-shaped threaded rebar having a diameter of 12 to 32 mm, the rolling start temperature is 1000 to 1100°C, and the finish rolling temperature is 850 to 950°C; In the temperature controlled cooling step, the rolled rod-shaped threaded reinforcing bar is naturally cooled on a cooling bed, and the temperature of the bar when it is transported to the cooling bed is 860 to 920°C.
[0021] Preferably, in both the process route 1 and the process route 2, in the hot continuous rolling step, the continuously cast billet is heated in a heating furnace, the heating temperature is 1080-1130°C, the residence time is 60-120 min, and then rolled into a coil-shaped threaded rebar having a diameter of 6-10 mm, the rolling start temperature is 980-1030°C, the finish rolling temperature is 850-950°C, and the laying temperature is 830-920°C.
[0022] Preferably, both the process route 1 and the process route 2 include an in-line pickling process and a packing process which are performed in sequence after the temperature-controlled cooling process, in which the rebar passes through a pickling tank, a passivation tank and a drying device in sequence, and the gas outlets of the pickling tank are distributed around the center line of the pickling tank.
[0023] Furthermore, when two reinforcing bars are joined as a welded sample by electroslag pressure welding, a breaking point in a tensile test of the obtained welded sample is formed in the base material of the two reinforcing bars.
[0024] Compared with the prior art, the beneficial effects of the present invention include:
[0025] (1) On the assumption of ultra-low carbon design, the respective contents of Cr, Mo, Mn, Ni, and Cu By rationally designing the relevant relationships and the respective contents and relevant relationships of C, N, Si, Mn, and Nb, the rebar contains a reasonable proportion of two-phase microstructure of ferrite and bainite, and the overall performance of the rebar is excellent. Specifically, the mechanical properties of the rebar are: yield strength ≧420MPa, tensile strength ≧540MPa, elongation at break ≧18%, and total elongation at maximum force ≧7.5%. In terms of corrosion resistance, in ambient immersion corrosion test and salt spray corrosion test, the corrosion resistance is improved by more than 45 times compared with ordinary HRB400. In electrochemical corrosion test, the self-corrosion potential is more than 0.4V in the noble band than ordinary HRB400, the polarization resistance is much higher than ordinary HRB400, and the self-corrosion current density is 1 / 65 or less than ordinary HRB400. Regarding welding performance, it is easy to weld, the weld structure is strong and difficult to break, and the breaking point in the tensile test of the welded sample is formed in the rebar base material.
[0026] (2) According to the above chemical composition design plan, it is possible to achieve excellent corrosion resistance, comprehensive mechanical properties and welding performance, while at the same time, the cost of alloying elements is low, energy saving and consumption is reduced, and it can be manufactured through multiple process routes, reducing the cost of the production process and being suitable for actual production and processing, with greater social significance and economic benefits.
[0027] In order to solve the technical problems existing in the prior art, the present invention aims to provide a method for producing 400 MPa-class corrosion-resistant rebar, which has excellent corrosion resistance, comprehensive mechanical performance and welding performance, has low material costs and process costs, and is suitable for wide use in marine construction.
[0028] In order to achieve the above object of the invention, one embodiment comprises: (1) A method for producing molten steel by sequentially performing a hot metal pre-desulfurization process, a converter smelting process, an AOD furnace refining process, and an LF furnace refining process, or a method for producing molten steel by sequentially performing a hot metal pre-desulfurization process, a converter smelting process, an LF furnace refining process, and an RH furnace refining process, and continuously casting the resulting molten steel into a steel billet, and a method for producing a steel billet having chemical compositions, in mass percent, of Cr: 9.5 to 10.4%, Mo: 1.0 to 1.2%, Mn: 0.3 to 0.6%, Ni: 0.01 to 1.00%, Cu: 0.01 to 0.05%, and Cu: 0.02 to 0.05%. a steelmaking step in which the content of Cr+Mo+0.5Mn+0.35Ni+0.25Cu is 11.1-12.2%, the content of C+N+0.3Si+Mn+1.8Nb is 0.4-0.8%, and the balance is Fe and unavoidable impurities; (2) Step 1 (This refers to the steelmaking step. The same applies below.) The steel billet obtained in step (a) is heated in a heating furnace at a heating temperature of 1100 to 1200°C and a residence time of 60 to 120 minutes. The steel billet is then rolled into a rod-shaped threaded rebar having a diameter of 12 to 32 mm. The rolling start temperature is 1000 to 1100°C and the finish rolling temperature is 850 to 950°C. The rolled rod-shaped threaded rebar is then naturally cooled on a cooling bed, and the temperature when it is transported to the cooling bed is 860 to 920°C. Alternatively, a method for producing 400 MPa class corrosion-resistant rebar is provided, comprising the steps of: heating the steel billet obtained in step 1 in a heating furnace at a heating temperature of 1080-1130°C and a residence time of 60-120 min; subsequently rolling the billet into a coil-shaped threaded rebar having a diameter of 6-10 mm; a rolling start temperature of 980-1030°C, a finish rolling temperature of 850-950°C, and a laying temperature of 830-920°C; and subsequently cooling the rolled coil-shaped threaded rebar by a delayed Stelmor cooling method, with all fans below the roller conveyor turned off.
[0029] Preferably, in step 1, the chemical composition of the steel billet further includes, in mass percent, any one or more of V: 0.1-0.15%, Ti: 0.01-0.05%, Al: 0.01-0.03%, and B: 0.0005-0.0020%.
[0030] Preferably, in step 1, when molten steel is smelted by sequentially using a hot metal pre-desulfurization step, a converter smelting step, an AOD furnace refining step, and an LF furnace refining step, the tapping temperature in the converter smelting step is 1600 to 1660°C, and in the AOD furnace refining step, a high carbon ferrochromium alloy and a molybdenum iron alloy are added to the molten steel to perform initial alloying of the molten steel, and after reduction and slag removal, a manganese alloy is added, the tapping ladle is purged with argon for 5 minutes or more before tapping, 20 kg of an aluminum ingot is added to the molten steel during tapping, the tapping temperature is 1630 to 1670°C, and the tapping temperature is 1630 to 1670°C. the content of is ≦0.01%; in the LF furnace refining process, after the molten steel reaches the ladle of the LF furnace, the slag is adjusted by adding 13-15 kg of lime and 4.0-6.5 kg of fluorite per ton of molten steel; the white slag holding time is ≧8 min; the soft stirring time is 8-15 min; the tapping temperature is 1600-1620°C; in the square billet continuous casting process, carbon-free mold flux or ultra-low carbon mold flux is used; the continuous casting temperature is 1520-1560°C; and the casting speed during continuous casting is 1.2-1.6 m / min; In the case where molten steel is smelted by sequentially using the hot metal preliminary desulfurization process, the converter smelting process, the LF furnace refining process, and the RH furnace refining process, in the converter smelting process, a trace carbon ferrochromium alloy is added to the molten steel during tapping to perform initial alloying of the molten steel, and the tapping temperature is 1700-1750°C; in the LF furnace refining process, argon is bottom-blown into the ladle of the LF furnace at a flow rate of 80-160 L / min throughout the entire process, and the tapping temperature is 1560-1600°C; in the RH furnace refining process, the RH furnace is evacuated for 3 min, and then oxygen blowing into the RH furnace is started, and the total amount of oxygen blown is 500-700 Nm 3 Then, a trace carbon ferrochrome alloy is added to the molten steel to After alloying, when the vacuum level is less than 2 mbar, clean water circulation treatment is performed for 5 minutes or more, the tapping temperature is 1560-1600°C, and the tapping C content is ≦0.015%. During the square billet continuous casting process, carbon-free mold flux or ultra-low carbon mold flux is used, the continuous casting temperature is 1520-1560°C, and the casting speed during continuous casting is 2.2-2.6 m / min.
[0031] Preferably, the method of production comprises: (3) Step 2 (This refers to the controlled rolling and controlled cooling steps. The same applies below.) The in-line pickling step includes passing the reinforcing bar obtained in step 3 through a pickling tank, a passivation tank and a drying device in order to perform in-line pickling, the gas outlets of the pickling tank are distributed around the center line of the pickling tank, and the reinforcing bar is packaged after leaving the drying device.
[0032] Furthermore, when two reinforcing bars manufactured by the above production method are joined as a welded sample by electroslag pressure welding, a breaking point in a tensile test of the obtained welded sample is formed in the base material of the two reinforcing bars.
[0033] Furthermore, the microstructure of the reinforcing bar produced by the above production method is ferrite and bainite, with the proportion of ferrite being 28% to 40%.
[0034] Furthermore, the reinforcing bars manufactured by the above-mentioned production method have A, B, C and D inclusions of the GB / T10561 standard of ≦1.0 grade.
[0035] Furthermore, the rebar produced by said production method has a yield strength of ≧420 MPa, a tensile strength of ≧540 MPa, an elongation at break of ≧18%, and a total elongation at maximum force of ≧7.5%.
[0036] Furthermore, the reinforcing bar manufactured by the above-mentioned production method has a corrosion rate of 0.05 to 0.1 g / (m) based on the average weight loss of the reinforcing bar in an ambient immersion corrosion test. 2 h) and salt spray corrosion test In the experiment, the corrosion rate due to the average weight loss of the rebar was 0.01 to 0.04 g / (m 2 · h) and In simulated concrete pore water with a chloride ion concentration of ≧3 mol / L, the self-corrosion potential of the reinforcing bar is -0.1 to -0.15 V and the polarization resistance is 2500 to 3000 kΩ / cm 2 in, Self-corrosion current density is ≦0.13μA / cm 2 It is.
[0037] Compared with the prior art, the beneficial effects of the present invention include:
[0038] (1) Under the premise of ultra-low carbon design, the content and related relationships of Cr, Mo, Mn, Ni, and Cu are reasonably designed, and the content and related relationships of C, N, Si, Mn, and Nb are reasonably designed, so that the rebar contains a two-phase microstructure of ferrite and bainite in a reasonable ratio, and the overall performance of the rebar is excellent. Specifically, the mechanical performance of the rebar is: yield strength ≧420MPa, tensile strength ≧540MPa, elongation at break ≧18%, and total elongation at maximum force ≧7.5%. In terms of corrosion resistance, in ambient immersion corrosion tests and salt spray corrosion tests, the corrosion resistance is more than 45 times higher than that of ordinary HRB400, and in electrochemical corrosion tests, the self-corrosion potential is more than 0.4V higher than that of ordinary HRB400 in the noble band, the polarization resistance is much higher than that of ordinary HRB400, and the self-corrosion current density is 1 / 65 or less than that of ordinary HRB400. Regarding welding performance, it is easy to weld, the weld structure is strong and difficult to break, and the breaking point in the tensile test of the welded sample is formed in the rebar base material.
[0039] (2) According to the above chemical composition design plan, it is possible to achieve excellent corrosion resistance, comprehensive mechanical properties and welding performance, while at the same time, the cost of alloying elements is low, energy saving and consumption is reduced, and it can be manufactured through multiple process routes, reducing the cost of the production process and being suitable for actual production and processing, with greater social significance and economic benefits.
[0040] (3) In addition, based on the above chemical composition design proposal, by combining process control in controlled rolling and controlled cooling, the structure, mechanical properties, corrosion resistance and weldability of the rebar can be further optimized, and the comprehensive performance of the rebar can be further improved. At the same time, the process operation in the hot continuous rolling process is simple and easy to control, and the smooth progress of the work situation in actual production can be guaranteed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0041] The technical solutions of the present invention are further illustrated below by specific embodiments, but the scope of the claimed invention is not limited by the description in the specification. First Embodiment
[0042] The present embodiment provides a corrosion-resistant rebar, in particular a hot-rolled deformed rebar, whose chemical composition, in mass percent, includes Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.50%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%, and the balance being Fe and unavoidable impurities.
[0043] In addition, the mass percentages of Cr, Mo, Mn, Ni and Cu in the chemical composition of the reinforcing bar further satisfy 11.1%≦Cr+Mo+0.5Mn+0.35Ni+0.25Cu≦12.2%, and the mass percentages of C, N, Si, Mn and Nb further satisfy 0.4%≦C+N+0.3Si+Mn+1.8Nb≦0.8%.
[0044] Here, the role of each chemical component in the reinforcing bar will be explained below.
[0045] Cr is an important corrosion-resistant element. It can form an oxide passivation film on the surface of reinforcing bars, effectively preventing the oxidation of reinforcing bars and improving the corrosion resistance of reinforcing bars. Especially when it coexists with elements such as Mo and Ni, the reinforcing bars can obtain better corrosion resistance and avoid the occurrence of pitting corrosion. In addition, the Cr element can improve the hardenability of the reinforcing bar. In the chemical composition design of the present invention, the Cr content is controlled to 9.5 to 10.4%.
[0046] Mo is an important corrosion-resistant element. In both reducing acid environments and strong oxidizing salt solution environments, the addition of Mo element can passivate the surface of the reinforcing bar, and can also prevent the pitting corrosion of the reinforcing bar in chloride solutions, thus improving the overall corrosion resistance of the reinforcing bar in various environments. In addition, the effect of Mo element in suppressing pearlite transformation is very significant, and at the same time, when combined with Cr, a carbide forming element, it can promote the formation of bainite. In addition, Mo element can promote the refinement of crystal grains and improve the hardenability and heat resistance of the reinforcing bar, but if the Mo content is too high, the oxidation resistance of the reinforcing bar will deteriorate. In the chemical composition design of the present invention, the Mo content is controlled to 1.0-1.2%.
[0047] Mn is a solid solution strengthening element that can increase the strength of the rough drawn wire and can also reduce the hot brittleness of the rebar in combination with the harmful element S. Mn is also important as a deoxidizer, desulfurizer, and austenite forming element. However, if the Mn content is too high, the plasticity, impact toughness, welding performance, etc. of the rebar are all reduced. In the chemical composition design of the present invention, the Mn content is controlled to 0.3 to 0.6%.
[0048] Ni is an important corrosion-resistant element, and Ni provides reinforcing bars with high corrosion resistance in acidic and alkaline environments, as well as high rust prevention and heat resistance at high temperatures. Ni is also an austenite-forming element, and can improve corrosion resistance by providing a uniform austenite structure to steel materials. In the chemical composition design of the present invention, the Ni content is controlled to 0.01 to 1.00%.
[0049] Cu is an important corrosion-resistant element and contributes to improving the corrosion resistance of rebars, but if the Cu content is too high, the plasticity of the steel material decreases and hot rolling cracks may occur. In the chemical composition design of the present invention, the Cu content is controlled to 0.01 to 0.50%.
[0050] C is an austenite forming element, and by controlling the carbon content to be below the solubility limit of ferrite, it is possible to improve the uniformity of the steel microstructure and component distribution, reduce the potential difference between each region inside the rebar, and lower the corrosion rate. In the chemical composition design of the present invention, the C content is controlled to 0.014% or less.
[0051] N is an austenite-forming element, and a high N content reduces the plasticity of the reinforcing bar and is also disadvantageous in controlling the ratio of ferrite and bainite in the reinforcing bar structure. In the chemical composition design of the present invention, the N content is controlled to 0.004% or less.
[0052] Nb is an element that strengthens microalloys, and can play the role of precipitation strengthening and grain refinement strengthening during the rolling process (for example, the hot continuous rolling process described later), but if the Nb content is too high, the plasticity of the reinforcing bar decreases and the cost increases. In the chemical composition design of the present invention, the Nb content is controlled to 0.01 to 0.05%.
[0053] Silicon is a solid solution strengthening element, and it dissolves in ferrite, inhibits the diffusion of carbon in austenite, delays the transformation of ferrite and pearlite, and can increase the yield strength and tensile strength of reinforcing bars. However, if the content of silicon is too high, the plasticity of the steel material decreases, and the welding performance of the reinforcing bars deteriorates. In the chemical composition design of the present invention, the content of silicon is controlled to 0.2 to 0.6%.
[0054] P can increase the strength and corrosion resistance of reinforcing bars, but it is prone to segregation in steel. If the P content is too high, the mechanical performance at low temperatures will decrease. In the chemical composition design of the present invention, the P content is The content is controlled to 0.01 to 0.03%.
[0055] Cr+Mo+0.5Mn+0.35Ni+0.25Cu is very important for the comprehensive control of the corrosion resistance, plasticity and cost of rebar. On the one hand, it can make the oxide film on the surface of rebar have sufficient density, improve the corrosion resistance and repair ability of the rebar skeleton, and ensure the corrosion resistance of the rebar oxide film and the rebar skeleton. On the other hand, it can avoid the low proportion of ferrite in the rebar structure, and is favorable for the control of the microstructure and its proportion of the rebar, thereby enhancing the plasticity of the rebar and increasing the elongation at break and the total elongation at maximum force. In yet another aspect, it can reduce the addition of precious alloy elements, reduce costs, and promote the generalization, design and use of construction. In the chemical component design of the present invention, Cr+Mo+0.5Mn+0.35Ni+0.25Cu meets 11.1-12.2%.
[0056] C+N+0.3Si+Mn+1.8Nb is very important for the comprehensive control of mechanical performance such as strength and plasticity of rebar. On the one hand, it ensures that alloy elements can fully exert the effects of solid solution strengthening, precipitation strengthening, microstructural strengthening, etc., and enhances the strength of rebar. On the other hand, it avoids a low proportion of ferrite in the rebar microstructure and a high proportion of bainite in the rebar microstructure, that is, it optimizes the respective proportions of ferrite and bainite in the rebar microstructure, enhances the plasticity of rebar, and increases the elongation at break and the total elongation at maximum force. In the chemical composition design of the present invention, C+N+0.3Si+Mn+1.8Nb meets 0.4-0.8%.
[0057] Generally speaking, compared with the prior art, the design of the chemical components of the present invention has the following advantages: (1) Under the premise of ultra-low carbon design, the content and related relationships of Cr, Mo, Mn, Ni, and Cu are reasonably designed, and the content and related relationships of C, N, Si, Mn, and Nb are reasonably designed, so that the microstructure of the rebar is ferrite and bainite, of which the proportion of ferrite is 28%-40% and the proportion of bainite is 60%-72%. In addition, the rebar has excellent corrosion resistance, comprehensive mechanical performance, and welding performance, and has excellent overall comprehensive performance, which is suitable for the use needs of marine engineering. (2) According to the above chemical component design plan, it can achieve excellent corrosion resistance, comprehensive mechanical performance, and welding performance, and at the same time, the cost of alloy elements is low, energy saving and consumption is reduced, and it can be manufactured through multiple process routes, which reduces the cost of the production process, is suitable for actual production and processing, and has higher social significance and economic effect.
[0058] Here, as described above, the microstructure of the reinforcing bar is ferrite and bainite, of which the proportion of ferrite is 28% to 40%, and the proportion of bainite is 60% to 72%. Thus, the influence of the microstructure of the reinforcing bar and the proportion of ferrite and bainite is specifically reflected in the following two aspects. One is the influence on mechanical performance, and by controlling the proportion of ferrite and bainite in this embodiment, appropriate yield strength and good elongation, including the elongation at break and the total elongation at maximum force, can be guaranteed, and good overall mechanical performance can be guaranteed. The other is the influence on corrosion resistance, and by ensuring a certain proportion of bainite structure, the corrosion resistance of the reinforcing bar can be improved.
[0059] Specifically, in terms of mechanical performance, the rebar is a rebar of 400 MPa class or above, with a yield strength of ≧420 MPa, a tensile strength of ≧540 MPa, an elongation at break of ≧18%, and a total elongation at maximum force of ≧7.5%.
[0060] In addition, the inclusions of the rebar are also well controlled, specifically, the A, B, C and D inclusions of the rebar in the GB / T10561 standard are all ≦1.0, thus improving the toughness of the rebar under low temperature conditions, which is favorable for ensuring the mechanical performance of the rebar.
[0061] Furthermore, in terms of corrosion resistance, ambient immersion corrosion tests and salt spray corrosion tests of the reinforcing bars showed that the corrosion resistance was improved by 45 times or more compared to normal HRB400. Specifically, in ambient immersion corrosion tests, the corrosion rate based on the average weight loss of the reinforcing bars was 0.05 to 0.1 g / (m 2 · h), and in a salt spray corrosion test, the corrosion rate based on the average weight loss of the reinforcing bar is 0.01 to 0.04 g / (m 2 h) and In simulated concrete pore water with a chloride ion concentration of ≧3 mol / L, the self-corrosion potential of the reinforcing bar is -0.1 to -0.15 V and the polarization resistance is 2500 to 3000 kΩ / cm 2 in, Self-corrosion current density is ≦0.13μA / cm 2 It is.
[0062] The specific method of the ambient immersion corrosion test used here is as follows: The treated sample is placed in an ambient immersion test box, and the test is performed in accordance with the YB / T4367 corrosion test method for rebar in a chloride ion environment, with the solution being 2.0±0.05 (wt%) NaCl, the pH being 6.5-7.2, the solution temperature being 45°C±2°C, and the drying temperature being 70°C±10°C, and the corrosion rate based on the average weight loss over 168 hours is obtained by continuous testing.
[0063] The specific method of the salt spray corrosion test used is as follows: the treated sample is placed in a salt spray test box, and the test is carried out in accordance with GB / T10125 Corrosion test in artificial atmosphere - Salt spray corrosion test, the solution is 2.0±0.05 (wt%) NaCl, the pH is 6.5-7.2, the solution temperature is 35℃±2℃, and the corrosion rate is obtained by the average weight loss in 168 hours by continuous testing.
[0064] In electrochemical corrosion tests, under the corrosion test conditions of simulated concrete pore water with a chloride ion concentration of ≧3 mol / L, the self-corrosion potential of the reinforcing steel is -0.1 to -0.15 V, which is 0.4 V more noble than that of normal HRB400. The polarization resistance of the reinforcing steel is 2500 to 3000 kΩ / cm 2 This is much higher than that of normal HRB400. Current density is ≦0.13μA / cm 2 This is 1 / 65 or less of the normal HRB400. Equivalent.
[0065] The specific method of the electrochemical corrosion test used here is as follows. The electrochemical test is performed in accordance with GB / T24196-2009 "Corrosion of metals and alloys / Electrochemical test methods / Guidelines for carrying out electrostatic potential polarization and potentiodynamic polarization measurements", using a three-electrode system, with a saturated calomel electrode as the reference electrode, a Pt sheet as the auxiliary electrode, and a simulated concrete pore water with a chloride ion concentration of ≥3 mol / L. The scanning range of the polarization curve test is -300~600 mV relative to the sample self-corrosion potential, and the scanning speed is 1 mV / s. The scanning frequency range of the electrochemical impedance test is 10 -2 ~10 5 Hz, and the AC excitation signal amplitude is ± It is 5mV.
[0066] From the above, in terms of corrosion resistance, the reinforcing bar has excellent corrosion resistance, and when corrosion performance tests were conducted in a simulated seawater solution, all of the indicators were found to be far superior to those of ordinary screw steel of the same grade.
[0067] Regarding weldability, the rebar is easy to weld, and when two of the rebars are joined as a welded specimen by electroslag pressure welding, the weld structure is strong and not easily broken, and the breaking point in a tensile test of the welded specimen is formed in the rebar base material, not at the weld position.
[0068] Preferably, in this embodiment, the nominal diameter of the reinforcing bar is 6 to 32 mm.
[0069] Here, when the nominal diameter of the reinforcing bar is 6-10 mm, the reinforcing bar is a coil reinforcing bar, and when the nominal diameter of the reinforcing bar is 12-32 mm, the reinforcing bar is a rod reinforcing bar. In this way, the requirements for reinforcing bars in marine construction can be met, and the diameter can be set. By designing the reinforced concrete structure, the overall mechanical performance and corrosion resistance of the reinforced concrete structure can be improved. <Second embodiment>
[0070] This embodiment provides a corrosion-resistant rebar, specifically a hot-rolled deformed rebar suitable for marine construction. The main difference from the first embodiment is that the performance of the rebar is further improved by further adding one or more of V: 0.1-0.15%, Ti: 0.01-0.05%, Al: 0.01-0.03%, and B: 0.0005-0.0020% to the chemical components.
[0071] Specifically, in this embodiment, the chemical components of the reinforcing bar include, in mass percent, any one or more of the following four elements: Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.50%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%, and V: 0.1-0.15%, Ti: 0.01-0.05%, Al: 0.01-0.03%, and B: 0.0005-0.0020%, with the remainder being Fe and unavoidable impurities.
[0072] Similarly to the first embodiment, the mass percentages of Cr, Mo, Mn, Ni and Cu in the chemical composition of the reinforcing bar further satisfy 11.1%≦Cr+Mo+0.5Mn+0.35Ni+0.25Cu≦12.2%, and the mass percentages of C, N, Si, Mn and Nb further satisfy 0.4%≦C+N+0.3Si+Mn+1.8Nb≦0.8%.
[0073] Here, the roles of elements such as Cr, Mo, Mn, Ni, Cu, C, N, Nb, Si, and P in the reinforcing bar and the design effects of Cr+Mo+0.5Mn+0.35Ni+0.25Cu and C+N+0.3Si+Mn+1.8Nb are the same as those in the first embodiment, and detailed explanations will be omitted. Below, the roles of the selective elements V, Ti, Al, and B in this embodiment will be explained.
[0074] V is an element that strengthens microalloys, and can precipitate V(C,N) compounds during the rolling process (for example, the hot continuous rolling process described later), which has a certain precipitation strengthening effect, as well as inhibiting the growth of austenite and ferrite grains and strengthening grain refinement. However, if the V content is too high, the plasticity of the reinforcing bar decreases and the cost increases. In the chemical composition design of the present invention, the V content is controlled to 0.1-0.15%.
[0075] Since Ti has a higher affinity with C element than Cr, it can prevent chromium carbide from precipitating and chromium deficiency at grain boundaries, and effectively prevent intergranular corrosion. In addition, when an appropriate amount of Ti is added, fine TiOx and TiN can be formed that are diffused and distributed in the steel sheet. However, if the Ti content is too high, the viscosity of the molten steel increases, which is disadvantageous for smelting the molten steel, and the size of the formed TiOx becomes coarse, which deteriorates the toughness of the steel sheet. In the chemical composition design of the present invention, the Ti content is controlled to 0.01 to 0.05%.
[0076] Al is a commonly used deoxidizer, which can increase the electrode potential of the rebar skeleton, improve corrosion resistance, and inhibit the growth of austenite grains to increase the strength of the rebar, but if the Al content is too high, the oxides in the steel will increase, which may impair the weldability of the rebar. In the chemical composition design of the present invention, the Al content is controlled to 0.01-0.03%.
[0077] B is a strengthening element and plays a significant role in improving rebar strength, but if the B content is too high, it is disadvantageous in improving intergranular corrosion resistance. In the chemical composition design of the present invention, the B content is controlled to 0.0005 to 0.0020%.
[0078] In this embodiment, by selectively adding any one or more of V, Ti, Al and B, the performance of the reinforcing bar can be further improved over that of the first embodiment, and the reinforcing bar has better corrosion resistance, mechanical strength, plasticity and welding performance, making construction easier and having a longer theoretical service life when used in marine construction. <Third embodiment>
[0079] This embodiment provides a method for producing a corrosion-resistant rebar, which can be used for both the production and manufacturing of the corrosion-resistant rebar of the first embodiment and the production and manufacturing of the corrosion-resistant rebar of the second embodiment.
[0080] In the present embodiment, the process path of the production method includes a hot metal pre-desulfurization process, a converter smelting process, an AOD furnace refining process, an LF furnace refining process, a square billet continuous casting process, a hot continuous rolling process, a temperature controlled cooling process, and a packaging process, which are performed in sequence. The production method will be described in detail below in the order of steps.
[0081] (1) Steelmaking step In this step, molten steel is smelted using a hot metal pre-desulfurization process, a converter smelting process, an AOD furnace refining process, and an LF furnace refining process in that order, and the obtained molten steel is continuously cast into a steel billet in the square billet continuous casting process.
[0082] When the above production method is used to manufacture the corrosion-resistant rebar of the first embodiment, it can be understood that the chemical composition of the steel billet obtained in this step is consistent with the chemical composition of the rebar of the first embodiment, that is, the chemical composition of the obtained steel billet is, in mass percent, Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.50%, It contains C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%, and Cr+Mo+0.5Mn+0.35Ni+0.25Cu is 11.1-12.2%, C+N+0.3Si+Mn+1.8Nb is 0.4-0.8%, and the balance is Fe and unavoidable impurities. Similarly, when the production method is used to manufacture the corrosion-resistant rebar of the second embodiment, the chemical composition of the steel billet obtained in this step is consistent with the chemical composition of the rebar of the second embodiment, that is, the chemical composition of the steel billet obtained is, in mass percent, Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.50%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%. %, S≦0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%, and contains one or more of the following four elements: V: 0.1-0.15%, Ti: 0.01-0.05%, Al: 0.01-0.03%, and B: 0.0005-0.0020%; and Cr+Mo+0.5Mn+0.35Ni+0.25Cu is 11.1-12.2%, C+N+0.3Si+Mn+1.8Nb is 0.4-0.8%, and the balance is Fe and unavoidable impurities.
[0083] Furthermore, the tapping temperature in the converter smelting process is 1600 to 1660° C., which ensures the effects of decarbonization and dephosphorization, and is advantageous for the subsequent alloying.
[0084] In the AOD furnace refining process, low-cost high-carbon ferrochrome alloy and molybdenum iron alloy are added to the molten steel after comprehensive consideration to perform initial alloying of the molten steel, and the slag is removed after reduction to reduce the content of impurities such as P. Then, manganese alloy is added to complete the initial alloying while deoxidizing. Before tapping, the ladle for tapping is purged with argon for more than 5 minutes, and the molten steel is cooled to 200°C. To reduce secondary oxidation, 20kg of aluminum ingot is added to the molten steel during tapping, the tapping temperature is 1630~1670℃, and the tapping C content is ≦0.01%, so as to ensure the decarbonization effect of the molten steel and the production tact time.
[0085] In the LF furnace refining process, after the molten steel reaches the ladle of the LF furnace, the slag is adjusted by adding 13-15 kg of lime and 4.0-6.5 kg of fluorite per ton of molten steel, the white slag holding time is ≥ 8 min, the soft stirring time is 8-15 min, and the tapping temperature is 1600-1620°C, so that the deoxidation and desulfurization of the molten steel is completed step by step.
[0086] In the square billet continuous casting process, the molten steel tapped from the LF furnace refining process is continuously cast into a billet, in which carbon-free mold flux or ultra-low carbon mold flux is used to prevent carbon from increasing in the molten steel, the temperature of continuous casting is 1520-1560°C, and the casting speed during continuous casting is 1.2-1.6 m / min to ensure continuous casting.
[0087] (2) Controlled rolling and controlled cooling In this step, the steel billet obtained in step 1 is rolled into a rebar with a nominal diameter of 6 to 32 mm by a hot continuous rolling process, and then a temperature controlled cooling process is carried out. The specific process scheme of this step varies depending on the nominal diameter of the rebar.
[0088] Specifically, in the case of a rebar with a nominal diameter of 12 to 32 mm, in the hot continuous rolling process, the steel billet obtained in step 1 is heated in a heating furnace, the heating temperature is 1100 to 1200 ° C, and the furnace time is 60 to 120 min, so that the alloy elements are sufficiently re-dissolved to be advantageous for the exertion of their strengthening effect. Then, the steel billet is rolled into a rod-shaped threaded rebar with a diameter of 12 to 32 mm, the rolling start temperature is 1000 to 1100 ° C, and the finish rolling temperature is 850 to 950 ° C, so that the austenite grains are maintained at a constant size. Then, in the temperature controlled cooling process, the rolled rod-shaped threaded rebar is naturally cooled in a cooling bed, and the temperature when it is transported to the cooling bed is 860 to 920 ° C, so that the size and ratio control of the subsequent ferrite and pearlite is guaranteed.
[0089] In the case of a rebar with a nominal diameter of 6 to 10 mm, in the hot continuous rolling process, the steel billet obtained in step 1 is heated in a heating furnace, the heating temperature is 1080 to 1130 ° C. so as to be favorable for sufficient re-dissolution of alloy elements, and the furnace time is 60 to 120 min. Then, it is rolled into a coil-shaped threaded rebar with a diameter of 6 to 10 mm, the rolling start temperature is 980 to 1030 ° C., the finish rolling temperature is 850 to 950 ° C., and the laying temperature is 830 to 920 ° C., so that the austenite grains are maintained at a constant size. Then, in the temperature controlled cooling process, the rolled coil-shaped threaded rebar is cooled by a delayed Stelmor method, all the blowers below the roller conveyor are turned off, and the ferrite and pearlite transformation is completed on the roller conveyor.
[0090] (3) Packaging The rebar cooled in step 2 is packed for transportation and use in construction.
[0091] As a result, the advantageous effects of the production method of this embodiment compared to the conventional technology are as follows.
[0092] (1) The chemical composition is designed based on the premise of ultra-low carbon, and the respective contents and related relationships of Cr, Mo, Mn, Ni, and Cu are rationally designed, and the respective contents and related relationships of C, N, Si, Mn, and Nb are rationally designed. The microstructure of the manufactured rebar is ferrite and bainite, of which the proportion of ferrite is 28% to 40%, and the proportion of bainite is 60% to 72%. In addition, the rebar has high corrosion resistance. It has excellent mechanical properties, excellent welding performance, and excellent overall performance, which is suitable for the use needs of marine engineering.
[0093] (2) According to the above chemical composition design plan, the process route is reasonable, especially the process control in controlled rolling and controlled cooling is reasonable, the overall performance of the obtained rebar is further optimized, there is no cracking defect during rolling, and the cost of alloying elements is low, energy saving and reducing consumption, the cost of the production process is reduced, it is suitable for actual production and processing, the process operation is simple and easy to control, and the smooth progress of the working situation in actual production is guaranteed, which has higher social significance and economic benefits. <Fourth embodiment>
[0094] This embodiment provides a method for producing a corrosion-resistant rebar, which can be used for both the production and manufacturing of the corrosion-resistant rebar of the first embodiment and the production and manufacturing of the corrosion-resistant rebar of the second embodiment.
[0095] In this embodiment, the process path of the production method includes a hot metal pre-desulfurization step, a converter smelting step, an LF furnace refining step, an RH furnace refining step, a square billet continuous casting step, a hot continuous rolling step, a temperature controlled cooling step, and a packaging step, which are performed in this order. That is, the difference between this embodiment and the third embodiment is only in the hot metal pre-desulfurization step, the converter smelting step, the LF furnace refining step, the RH furnace refining step, and the square billet continuous casting step, i.e., only in the steelmaking step. Hereinafter, the production method of this embodiment will be described in detail with respect to only the steelmaking step.
[0096] (1) Steelmaking step In this step, molten steel is smelted using a hot metal pre-desulfurization process, a converter smelting process, an LF furnace refining process, and an RH furnace refining process in that order, and the obtained molten steel is continuously cast into a steel billet in the square billet continuous casting process.
[0097] When the above production method is used to manufacture the corrosion-resistant rebar of the first embodiment, it can be understood that the chemical composition of the steel billet obtained in this step is consistent with the chemical composition of the rebar of the first embodiment, that is, the chemical composition of the obtained steel billet is, in mass percent, Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.50%, It contains C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%, and Cr+Mo+0.5Mn+0.35Ni+0.25Cu is 11.1-12.2%, C+N+0.3Si+Mn+1.8Nb is 0.4-0.8%, and the balance is Fe and unavoidable impurities. Similarly, when the production method is used to manufacture the corrosion-resistant rebar of the second embodiment, the chemical composition of the steel billet obtained in this step is consistent with the chemical composition of the rebar of the second embodiment, that is, the chemical composition of the steel billet obtained is, in mass percent, Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.50%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%. %, S≦0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%, and contains one or more of the following four elements: V: 0.1-0.15%, Ti: 0.01-0.05%, Al: 0.01-0.03%, and B: 0.0005-0.0020%; and Cr+Mo+0.5Mn+0.35Ni+0.25Cu is 11.1-12.2%, C+N+0.3Si+Mn+1.8Nb is 0.4-0.8%, and the balance is Fe and unavoidable impurities.
[0098] Furthermore, in the converter smelting process, a trace amount of carbon ferrochrome alloy is added to the molten steel during tapping to perform initial alloying of the molten steel, and the C content in the molten steel is controlled as much as possible in terms of alloy addition, and the efficiency is improved. The tapping temperature is 1700-1750℃ to ensure the dephosphorization effect and prepare for the subsequent smelting.
[0099] During the LF furnace refining process, argon is blown into the ladle of the LF furnace at a flow rate of 80-160 L / min from the bottom throughout the process, and the tapping temperature is 1560-1600°C, which ensures the melting and homogenization of the alloy in the ladle and is favorable for controlling the production tact time.
[0100] During the RH furnace refining process, the RH furnace is evacuated for 3 minutes, and then oxygen is blown into the RH furnace. The total amount of oxygen blown is 500 to 700 Nm 3 Then, trace amounts of carbon and phenyl are added to the molten steel. Add Cr alloy to alloy the molten steel. As the Cr alloying is completed step by step, the carbon increase in the molten steel decreases. When the vacuum level is less than 2mbar, the steel is circulated with fresh water for 5min or more. The tapping temperature is 1560~1600℃ and the tapping C content is ≦0.015% to ensure the decarbonization effect.
[0101] In the square billet continuous casting process, the molten steel tapped from the LF furnace refining process is continuously cast into a billet, in which carbon-free mold flux or ultra-low carbon mold flux is used to prevent carbon from increasing in the molten steel, the temperature of continuous casting is 1520-1560°C, and the casting speed during continuous casting is 2.2-2.6m / min, which is advantageous for continuous casting.
[0102] As described above, the controlled rolling and controlled cooling step in step 2 and the packaging step in step 3 are both similar to those in the third embodiment, and therefore detailed description thereof will be omitted.
[0103] As a result, the advantageous effects of the production method of this embodiment compared to the conventional technology are as follows.
[0104] (1) The chemical composition is designed based on the premise of ultra-low carbon design, and the contents and related relationships of Cr, Mo, Mn, Ni, and Cu are reasonably designed, and the contents and related relationships of C, N, Si, Mn, and Nb are reasonably designed, so that the microstructure of the manufactured rebar is ferrite and bainite, of which the proportion of ferrite is 28%-40% and the proportion of bainite is 60%-72%. In addition, the rebar has excellent corrosion resistance, comprehensive mechanical performance and welding performance, and has excellent overall performance, which is suitable for the use needs of marine engineering.
[0105] (2) According to the above chemical composition design plan, the process route is reasonable, especially the process control in controlled rolling and controlled cooling is reasonable, the overall performance of the obtained rebar is further optimized, there is no cracking defect during rolling, and the cost of alloying elements is low, energy saving and reducing consumption, the cost of the production process is reduced, it is suitable for actual production and processing, the process operation is simple and easy to control, and the smooth progress of the working situation in actual production is guaranteed, which has higher social significance and economic benefits. <Fifth embodiment>
[0106] The present embodiment provides a method for producing corrosion-resistant rebar, the process path of which includes a hot metal pre-desulfurization process, a converter smelting process, an LF furnace refining process, an RH furnace refining process, a square billet continuous casting process, a hot continuous rolling process, a temperature-controlled cooling process, an in-line pickling process, and a packaging process, which are performed in sequence.
[0107] In this embodiment, the steps from the hot metal pre-desulfurization step to the temperature controlled cooling step may be carried out in the third embodiment or in the fourth embodiment. That is, this embodiment is based on the third or fourth embodiment, and an in-line pickling step is added before the packaging step. Hereinafter, only the in-line pickling step will be described, and other detailed descriptions will be omitted.
[0108] Specifically, in the in-line pickling process, i.e., after the temperature-controlled cooling process and before the packaging process, the rebar is passed through a pickling tank, a passivation tank and a drying device in order to realize the in-line pickling of the rebar, where the gas outlets of the pickling tank are distributed around the center line of the pickling tank to enhance the effect of pickling.
[0109] The present invention will be further described below by providing Examples 1 to 16 of the present invention. It is understood that the following are only a part of the preferred examples of the present invention, and are not all of the embodiments of the present invention, and other examples carried out based on the above embodiments do not deviate from the technical gist of the present invention.
[0110] First, in Examples 1 to 16 and Comparative Examples 1 to 4, reinforcing bars are provided, and the chemical components of the reinforcing bars are as shown in Table 1. Among them, Example 12 is implemented in the first embodiment described in the present invention, the other Examples are implemented in the second embodiment described in the present invention, and Comparative Examples 1 to 4 do not meet any of the embodiments of the present invention.
[0111] [Table 1]
[0112] The production methods of Examples 1 to 8 employ a process path including a hot metal pre-desulfurization process, a converter smelting process, an AOD furnace refining process, an LF furnace refining process, a square billet continuous casting process, a hot continuous rolling process, a temperature controlled cooling process, and an in-line pickling process, which are carried out in this order. Each process will be described below.
[0113] (1) In the molten iron pre-desulfurization process, the molten iron is pre-desulfurized.
[0114] (2) In the converter smelting process, the tapping temperature is 1600 to 1660°C.
[0115] (3) In the AOD furnace refining process, high carbon ferrochromium alloy and molybdenum iron alloy are added to the molten steel to perform initial alloying of the molten steel, and after reduction and slag removal, manganese alloy is added. Before tapping, the tapping ladle is purged with argon for more than 5 minutes. 20 kg of aluminum ingot is added to the molten steel during tapping. The tapping temperature is 1630-1670℃, and the tapping C content is ≦0.010%. It is.
[0116] (4) In the LF furnace refining process, after the molten steel reaches the ladle of the LF furnace, the slag is adjusted by adding 13-15 kg of lime and 4.0-6.5 kg of fluorite per ton of molten steel, the white slag holding time is ≧8 min, the soft stirring time is 8-15 min, and the tapping temperature is 1600-1620 °C.
[0117] (5) In the square billet continuous casting process, the molten steel tapped in the LF furnace refining process is continuously cast into a billet, in which a carbon-free mold flux or an ultra-low carbon mold flux is used, the continuous casting temperature is 1520-1560°C, and the casting speed during continuous casting is 1.2-1.6 m / min.
[0118] (6) In the hot continuous rolling process, in Examples 1 to 4, the billet is heated in a heating furnace, the heating temperature is 1100 to 1200°C, the furnace time is 60 to 120 min, and then rolled into a rod-shaped threaded rebar with a diameter of 12 to 32 mm, the rolling start temperature is 1000 to 1100°C, and the finish rolling temperature is 850 to 950°C. In Examples 5 to 8, the billet is heated in a heating furnace, the heating temperature is 1080 to 1130°C, the furnace time is 60 to 120 min, and then rolled into a coil-shaped threaded rebar with a diameter of 6 to 10 mm, the rolling start temperature is 980 to 1030°C, the finish rolling temperature is 850 to 950°C, and the laying temperature is 830 to 920°C.
[0119] (7) In the temperature-controlled cooling process, in Examples 1 to 4, the rolled rod-shaped threaded reinforcing bars are naturally cooled on a cooling bed, and the temperature when transported to the cooling bed is 860 to 920°C. In Examples 5 to 8, the rolled coil-shaped threaded reinforcing bars are cooled by a delayed Stelmor method, and all fans below the roller conveyor are turned off.
[0120] (8) In the in-line pickling process, the reinforcing bar is passed through a pickling tank, a passivation tank and a drying device in order to realize the in-line pickling of the reinforcing bar, in which the gas outlets of the pickling tank are distributed around the center line of the pickling tank, and then packaged.
[0121] The production methods of Examples 9 to 16 employ process routes including a molten iron pre-desulfurization process, a converter smelting process, an LF furnace refining process, an RH furnace refining process, a square billet continuous casting process, a hot continuous rolling process, a temperature controlled cooling process, and an in-line pickling process, which are carried out in this order. Each process will be described below.
[0122] (1) In the hot metal pre-desulfurization process, the hot metal is pre-desulfurized, and after desulfurization, the S content is ≦0.001% and the slag removal rate is ≧95%.
[0123] (2) In the converter smelting process, a trace carbon ferrochromium alloy is added to the molten steel during tapping to perform initial alloying of the molten steel, and the tapping temperature is 1700-1750°C.
[0124] (3) In the LF furnace refining process, argon is blown into the ladle of the LF furnace at a bottom flow rate of 80 to 160 L / min throughout the entire process, and the tapping temperature is 1560 to 1600°C.
[0125] (4) In the RH furnace refining process, the RH furnace is evacuated for 3 min, and then oxygen is blown into the RH furnace. The total amount of oxygen blown is 500-700 Nm 3 Then, trace carbon filaments are added to the molten steel. Adding ferrochrome alloy to alloy molten steel, circulating fresh water for 5 minutes or more when vacuum level is less than 2mbar, tapping temperature is 1560-1600℃, and C content is ≦0.015%.
[0126] (5) In the square billet continuous casting process, the molten steel tapped from the LF furnace refining process is cast into billets. Continuous casting is performed, in which carbon-free mold flux or ultra-low carbon mold flux is used, the temperature of continuous casting is 1520-1560°C, and the casting speed during continuous casting is 2.2-2.6m / min.
[0127] (6) In the hot continuous rolling process, in Examples 9 to 12, the billet is heated in a heating furnace, the heating temperature is 1100 to 1200°C, the furnace time is 60 to 120 min, and then rolled into a rod-shaped threaded rebar with a diameter of 12 to 32 mm, the rolling start temperature is 1000 to 1100°C, and the finish rolling temperature is 850 to 950°C. In Examples 13 to 16, the billet is heated in a heating furnace, the heating temperature is 1080 to 1130°C, the furnace time is 60 to 120 min, and then rolled into a coil-shaped threaded rebar with a diameter of 6 to 10 mm, the rolling start temperature is 980 to 1030°C, the finish rolling temperature is 850 to 950°C, and the laying temperature is 830 to 920°C.
[0128] (7) In the temperature-controlled cooling process, in Examples 9 to 12, the rolled rod-shaped threaded reinforcing bars are naturally cooled on a cooling bed, and the temperature when transported to the cooling bed is 860 to 920°C. In Examples 13 to 16, the rolled coil-shaped threaded reinforcing bars are cooled by a delayed Stelmor method, and all fans below the roller conveyor are turned off.
[0129] (8) In the in-line pickling process, the reinforcing bar is passed through a pickling tank, a passivation tank and a drying device in order to realize the in-line pickling of the reinforcing bar, in which the gas outlets of the pickling tank are distributed around the center line of the pickling tank, and then packed.
[0130] The production methods used in Comparative Examples 1 to 4 are the conventional process routes of converter smelting, square billet continuous casting, hot continuous rolling, and cooling on a cooling bed, among which, during the hot continuous rolling process, the heating temperature in the heating furnace is 1210 to 1290°C, the rolling start temperature is 1090 to 1170°C, the temperature when transported to the cooling bed is ≧1100°C, and the steel is naturally cooled in the cooling bed.
[0131] The reinforcing bars of Examples 1 to 16 and Comparative Examples 1 to 4 were sampled using the same test method to detect their mechanical performance. The mechanical performance of each of the Examples and Comparative Examples is as shown in Table 2.
[0132] As can be seen from Table 2, Examples 1 to 16 are clearly superior to Comparative Examples 1 to 4 in terms of mechanical performance, and meet the requirements for 400 MPa-class earthquake-resistant rebar, with a yield strength of ≧420 MPa, a tensile strength of ≧540 MPa, an elongation at break of ≧18%, and a total elongation at maximum force of ≧7.5%.
[0133] [Table 2]
[0134] The reinforcing bars of Examples 1 to 16 and Comparative Examples 1 to 4 were subjected to ambient immersion corrosion tests, salt spray corrosion tests, and electrochemical corrosion tests by the same method. The test results are shown in Table 3.
[0135] The specific method of the ambient immersion corrosion test used is as follows: The treated sample is placed in an ambient immersion test box, and the test is performed in accordance with the YB / T4367 corrosion test method for rebar in a chloride ion environment, with the solution being 2.0±0.05 (wt%) NaCl, pH 6.5-7.2, solution temperature 45°C±2°C, and drying temperature 70°C±10°C, and the corrosion rate is obtained by the average weight loss over 168 hours through continuous testing.
[0136] The specific method of the salt spray corrosion test used is as follows: the treated sample is placed in a salt spray test box, and the test is carried out in accordance with GB / T10125 Corrosion test in artificial atmosphere - Salt spray corrosion test, the solution is 2.0±0.05 (wt%) NaCl, the pH is 6.5-7.2, the solution temperature is 35℃±2℃, and the corrosion rate is obtained by the average weight loss in 168 hours by continuous testing.
[0137] The specific method of the electrochemical corrosion test used is as follows. The electrochemical test is performed in accordance with GB / T24196-2009 "Corrosion of metals and alloys / Electrochemical test methods / Guidelines for the implementation of electrostatic potential polarization and potentiodynamic polarization measurements", using a three-electrode system, the reference electrode is a saturated calomel electrode, the auxiliary electrode is a Pt sheet, and the test solution is simulated concrete pore water with a chloride ion concentration of ≧3mol / L. The scanning range of the polarization curve test is -300~600mV relative to the sample self-corrosion potential, and the scanning speed is 1mV / s. The scanning frequency range of the electrochemical impedance test is 10 -2 ~10 5 Hz, AC excitation signal amplitude is ±5mV be.
[0138] [Table 3]
[0139] As can be seen from Table 3, Examples 1 to 16 are significantly superior in terms of corrosion resistance to Comparative Examples 1 to 4. In the ambient immersion corrosion test, the corrosion rate based on the average weight loss of the reinforcing steel was 0.05 to 0.1 g / (m 2 h), and in a salt spray corrosion test, the average weight loss of the reinforcing bar is The corrosion rate due to loss is 0.01 to 0.04 g / (m 2 h) Corrosion resistance is normal HRB400 In electrochemical corrosion tests, the self-corrosion potential of the reinforcing steel is -0.1 to -0.15 V in simulated concrete pore water with a chloride ion concentration of ≥ 3 mol / L, which is 0.4 V more noble than that of normal HRB400. The polarization resistance of the reinforcing steel is 2500 to 3000 kΩ / cm 2 This is much higher than the normal HRB400. The self-corrosion current density of rebar is ≦0.13μA / cm 2 This is 1 / 6 of the normal HRB400. Equivalent to 5 or less.
[0140] In addition, the reinforcing bars of Examples 1 to 16 were sampled to detect inclusions and microstructures. As a result, the A, B, C, and D inclusions in the GB / T10561 standard were all ≦1.0 grade, and the microstructure was ferrite and bainite, of which ferrite was predominant. The proportion of ferrite is 28% to 40%, and the proportion of bainite is 60% to 72%.
[0141] In addition, the rebars of Examples 1 to 16 were sampled and subjected to a welding test by electroslag pressure welding. The welded samples were subjected to a tensile test in accordance with the room temperature test method standard of Part 1 of the tensile test for metallic materials of GBT228.1-2010. As a result, it was found that the fracture point in the tensile test of the welded samples was formed not at the position of the welded point but in the base material of the rebar, and the welded performance of the obtained rebars was excellent.
Claims
1. Chemical composition in mass percent: Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.5%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦0.004%, O≦0.00 3%, As≦0.01%, P: 0.01-0.03%, Cr+Mo+0.5Mn+0.35Ni+0.25Cu is 11.1-12.2%, C+N+0.3Si+Mn+1.8Nb is 0.4-0.8%, and the balance is Fe and unavoidable impurities.
2. The 400 MPa class corrosion-resistant rebar according to claim 1, further comprising, in mass percent, any one or more of V: 0.1-0.15%, Ti: 0.01-0.05%, Al: 0.01-0.03%, and B: 0.0005-0.0020%.
3. The 400 MPa class corrosion-resistant reinforcing bar according to claim 1, characterized in that the microstructure is ferrite and bainite, with the proportion of ferrite being 28% to 40%.
4. 2. The 400 MPa class corrosion-resistant reinforcing bar according to claim 1, wherein the A, B, C and D type inclusions in the GB / T10561 standard are all ≦1.0 grade.
5. 2. The 400 MPa class corrosion resistant rebar according to claim 1, characterized in that it has a yield strength of ≥ 420 MPa, a tensile strength of ≥ 540 MPa, an elongation at break of ≥ 18%, and a total elongation at maximum force of ≥ 7.5%.
6. The 400 MPa class corrosion-resistant rebar according to claim 1, characterized in that the nominal diameter is 6 to 32 mm.
7. The 400 MPa class corrosion-resistant reinforcing bar according to claim 6, characterized in that it is a coil-shaped reinforcing bar having a nominal diameter of 6 to 10 mm, or a rod-shaped reinforcing bar having a nominal diameter of 12 to 32 mm.
8. In ambient immersion corrosion tests, the corrosion rate based on average weight loss is 0.05 to 0.1 g / (m 2 h), and in a salt spray corrosion test, the corrosion rate based on average weight loss is 0.01 to 0.04 g / (m 2 h) In simulated concrete pore water with a chloride ion concentration of ≧3 mol / L, the self-corrosion potential is −0.1 to −0.15 V and the polarization resistance is 2500 to 3000 kΩ / cm 2 and the self-corrosion current density is ≦0.13 μA / cm 2 400MP according to claim 1, characterized in that Class A corrosion resistant steel bars.
9. The chemical composition is, in mass percent, Cr: 9.5-10.4%, Mo: 1.0-1.2%, Mn: 0.3-0.6%, Ni: 0.01-1.00%, Cu: 0.01-0.5%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦0.004%, O≦0.00 3%, As≦0.01%, P: 0.01-0.03%, Cr+Mo+0.5Mn+0.35Ni+0.25Cu is 11.1-12.2%, C+N+0.3Si+Mn+1.8Nb is 0.4-0.8%, and the balance is Fe and unavoidable impurities. Either process path 1 or process path 2 is used, The process path 1 includes a hot metal pre-desulfurization process, a converter smelting process, an AOD furnace refining process, an LF furnace refining process, a square billet continuous casting process, a hot continuous rolling process, and a temperature controlled cooling process, which are performed in sequence. The process path 2 is a method for producing a 400 MPa-class corrosion-resistant rebar, which is characterized by including a molten iron pre-desulfurization process, a converter smelting process, an LF furnace refining process, an RH furnace refining process, a square billet continuous casting process, a hot continuous rolling process, and a temperature-controlled cooling process, which are performed in this order.
10. In the process path 1, The tapping temperature of the converter smelting process is 1600 to 1660°C, In the AOD furnace refining process, a high carbon ferrochromium alloy and a molybdenum iron alloy are added to the molten steel to perform initial alloying of the molten steel, and after reduction and slag removal, a manganese alloy is added. Before tapping, the tapping ladle is purged with argon for 5 minutes or more. 20 kg of aluminum ingot is added to the molten steel during tapping. The tapping temperature is 1630-1670°C, and the tapping C content is ≦0.010%. In the LF furnace refining process, after the molten steel reaches the ladle of the LF furnace, slag is adjusted by adding 13 to 15 kg of lime and 4.0 to 6.5 kg of fluorite per ton of molten steel, the white slag holding time is ≧8 min, the soft stirring time is 8 to 15 min, and the tapping temperature is 1600 to 1620 ° C., 10. The method for producing a 400 MPa-class corrosion-resistant rebar as claimed in claim 9, characterized in that in the square billet continuous casting process, carbon-free mold flux or ultra-low carbon mold flux is used, the temperature of continuous casting is 1520-1560°C, and the casting speed during continuous casting is 1.2-1.6 m / min.
11. In the process path 2, In the converter smelting process, a trace carbon ferrochrome alloy is added to the molten steel during tapping to perform initial alloying of the molten steel, and the tapping temperature is 1700 to 1750°C; During the LF furnace refining process, argon is blown from the bottom into the ladle of the LF furnace at a flow rate of 80 to 160 L / min throughout the process, and the tapping temperature is 1560 to 1600°C; During the RH furnace refining process, the RH furnace is evacuated for 3 minutes, and then oxygen is blown into the RH furnace at a total volume of 500 to 700 Nm 3 Then, a trace carbon ferrochrome alloy is added to the molten steel to alloy the molten steel. When the vacuum level is less than 2 mbar, fresh water circulation is performed for 5 min or more. The tapping temperature is 1560-1600°C, and the tapping C content is ≦0.015%.
10. The method for producing a 400 MPa-class corrosion-resistant rebar as claimed in claim 9, characterized in that in the square billet continuous casting process, carbon-free mold flux or ultra-low carbon mold flux is used, the temperature of continuous casting is 1520-1560°C, and the casting speed during continuous casting is 2.2-2.6 m / min.
12. In both the process path 1 and the process path 2, In the hot continuous rolling process, the continuous cast billet is heated in a heating furnace, the heating temperature is 1100 to 1200°C, the furnace time is 60 to 120 min, and then rolled into a rod-shaped threaded rebar having a diameter of 12 to 32 mm, the rolling start temperature is 1000 to 1100°C, and the finish rolling temperature is 850 to 950°C. The method for producing a 400 MPa-class corrosion-resistant rebar according to claim 9, characterized in that during the temperature-controlled cooling process, the rolled rod-shaped threaded rebar is naturally cooled on a cooling bed, and the temperature when it is transported to the cooling bed is 860 to 920 ° C.
13. In both the process path 1 and the process path 2, The method for producing a 400 MPa-class corrosion-resistant rebar according to claim 9, characterized in that, in the hot continuous rolling process, the continuously cast billet is heated in a heating furnace at a heating temperature of 1080-1130°C and a residence time of 60-120 min, and then rolled into a coil-shaped threaded rebar having a diameter of 6-10 mm, the rolling start temperature being 980-1030°C, the finish rolling temperature being 850-950°C, and the laying temperature being 830-920°C.
14. Both process route 1 and process route 2 include an in-line pickling step and a packaging step, which are performed in sequence after the temperature controlled cooling step; 10. The method for producing 400 MPa-class corrosion-resistant rebars according to claim 9, wherein in the in-line pickling process, the rebars are passed through a pickling tank, a passivation tank and a drying device in this order, and the gas outlets of the pickling tank are distributed around the center line of the pickling tank.
15. (1) A method for producing molten steel by sequentially performing a hot metal pre-desulfurization process, a converter smelting process, an AOD furnace refining process, and an LF furnace refining process, or a method for producing molten steel by sequentially performing a hot metal pre-desulfurization process, a converter smelting process, an LF furnace refining process, and an RH furnace refining process, and continuously casting the resulting molten steel into a steel billet, wherein the chemical composition of the steel billet is, in mass percent, Cr: 9.5 to 10.4%, Mo: 1.0 to 1.2%, Mn: 0.3 to 0.6%, Ni: 0.01 to 1.00%, Cu: 0.01 to 0.05%, and Cu: 0.02 to 0.05%. 0.01-0.5%, C≦0.014%, N≦0.004%, Nb: 0.01-0.05%, Si: 0.2-0.6%, S≦0.004%, O≦0.003%, As≦0.01%, P: 0.01-0.03%, and Cr+Mo+0.5Mn+0.35Ni+0.25Cu is 11.1-12.2%, C+N+0.3Si+Mn+1.8Nb is 0.4-0.8%, and the balance is Fe and unavoidable impurities; (2) The steel billet obtained in the steelmaking step is heated in a heating furnace, the heating temperature is 1100 to 1200°C, and the furnace time is 60 to 120 min. Then, the steel billet is rolled into a rod-shaped threaded rebar having a diameter of 12 to 32 mm, the rolling start temperature is 1000 to 1100°C, and the finish rolling temperature is 850 to 950°C. Then, the rolled rod-shaped threaded rebar is naturally cooled on a cooling bed, and the temperature when it is transported to the cooling bed is 860 to 920°C. Alternatively, the steel billet obtained in the steel making step is heated in a heating furnace at a heating temperature of 1080 to 1130°C and a residence time of 60 to 120 min, and then rolled into a coil-shaped threaded rebar having a diameter of 6 to 10 mm at a rolling start temperature of 980 to 1030°C, a finish rolling temperature of 850 to 950°C, and a laying temperature of 830 to 920°C. Thereafter, the rolled coil-shaped threaded rebar is cooled by Stelmor cooling, and a controlled rolling / controlled cooling step is included in which all fans below the roller conveyor are turned off.
16. The method for producing 400 MPa-class corrosion-resistant rebar as described in claim 15, characterized in that in the steelmaking step, the chemical composition of the steel billet further includes, in mass percent, any one or more of V: 0.1-0.15%, Ti: 0.01-0.05%, Al: 0.01-0.03%, and B: 0.0005-0.0020%.
17. In the steelmaking step, when molten steel is smelted using a hot metal preliminary desulfurization process, a converter smelting process, an AOD furnace refining process, and an LF furnace refining process in this order, the tapping temperature in the converter smelting process is 1600 to 1660°C, and in the AOD furnace refining process, a high carbon ferrochromium alloy and a molybdenum iron alloy are added to the molten steel to perform initial alloying of the molten steel, and after reduction and slag removal, a manganese alloy is added, the tapping ladle is purged with argon for 5 minutes or more before tapping, 20 kg of an aluminum ingot is added to the molten steel during tapping, the tapping temperature is 1630 to 1670°C, and tapping C In the LF furnace refining process, after the molten steel reaches the ladle of the LF furnace, 13-15 kg of lime and 4.0-6.5 kg of fluorite are added per ton of molten steel to adjust the slag, the white slag holding time is ≥8 min, the soft stirring time is 8-15 min, and the tapping temperature is 1600-1620°C. In the square billet continuous casting process, carbon-free mold flux or ultra-low carbon mold flux is used, the continuous casting temperature is 1520-1560°C, and the casting speed during continuous casting is 1.2-1.6 m / min. In the case where molten steel is smelted by sequentially using a hot metal preliminary desulfurization process, a converter smelting process, an LF furnace refining process, and an RH furnace refining process, in the converter smelting process, a trace carbon ferrochrome alloy is added to the molten steel during tapping to perform initial alloying of the molten steel, and the tapping temperature is 1700 to 1750°C; in the LF furnace refining process, argon is bottom-blown into the ladle of the LF furnace at a flow rate of 80 to 160 L / min throughout the entire process, and the tapping temperature is 1560 to 1600°C; and in the RH furnace refining process, the RH furnace is evacuated for 3 minutes, and then oxygen blowing into the RH furnace is started, and the total amount of oxygen blown is 1000 to 2000°C. 500-700Nm 3 Then, a trace carbon ferrochrome alloy is added to the molten steel to The method for producing a 400 MPa-class corrosion-resistant rebar according to claim 15, characterized in that, when the alloying is performed and the vacuum degree becomes smaller than 2 mbar, fresh water circulation treatment is performed for 5 min or more; the tapping temperature is 1560-1600°C, the tapping C content is ≦0.015%, and in the square billet continuous casting process, carbon-free mold flux or ultra-low carbon mold flux is used; the continuous casting temperature is 1520-1560°C, and the casting speed during continuous casting is 2.2-2.6 m / min.
18. (3) The method for producing 400 MPa-class corrosion-resistant rebars according to claim 15, further comprising an in-line pickling step of passing the rebar obtained in the controlled rolling and controlled cooling steps through a pickling tank, a passivation tank and a drying device in order to perform in-line pickling, the gas outlets of the pickling tank are distributed around the center line of the pickling tank, and the rebar is packaged after leaving the drying device.
Citation Information
Patent Citations
Anti-corrosion reinforcing steel bar capable of increasing concrete structure durability and preparation method thereof
CN107641757A
Corrosion-resistant steel bar and production method of corrosion-resistant steel bar
CN113528962A
Cr STEEL FOR REINFORCING ROD HAVING EXCELLENT MECHANICAL PROPERTY AND CORROSION RESISTANCE IN CONCRETE
JP2007197786A
Ultra-high strength rebar
US20140237935A1